2017
DOI: 10.18632/oncotarget.18752
|View full text |Cite
|
Sign up to set email alerts
|

Association between LMP2/LMP7 genetic variability and cancer susceptibility, especially among Asians: evidence from a meta-analysis

Abstract: Low molecular mass protein (LMP) gene performs a critical role in the foreign antigen processing machine via the major histocompatibility complex-I (MHC-I) complex CD8+ cytotoxic T lymphocytes (CTL) pathway. Recent studies have reported the association of LMP2-60 G>A (rs17587) and LMP7-145 C>A (rs2071543) polymorphisms with various types of cancers, but the outcomes remained inconsistent. To obtain a reliable conclusion, we summarized available data and conducted a meta-analysis involving a total of 19 publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The body relies on MHC-I-restricted T cells to eliminate cancer cells. In their study, Wu et al showed that certain polymorphisms of LMP proteins (rs17587 and rs2071543 polymorphisms) were associated with an increased cancer risk in the recessive and homozygote models [ 16 ]. Similarly, in another study, a role was shown for polymorphisms of enzymes involved in phase I metabolism but not phase II metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…The body relies on MHC-I-restricted T cells to eliminate cancer cells. In their study, Wu et al showed that certain polymorphisms of LMP proteins (rs17587 and rs2071543 polymorphisms) were associated with an increased cancer risk in the recessive and homozygote models [ 16 ]. Similarly, in another study, a role was shown for polymorphisms of enzymes involved in phase I metabolism but not phase II metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Wu et al [17] conducted a meta-analysis of 19 published studies and reported that the PSMB9 rs17587 and PSMB8 rs2071543 SNPs were associated with increased cancer risk in the recessive model [17]. Furthermore, when these data were filtered by cancer type, individuals with the PSMB9 rs17587 SNP were more susceptible to gynecological cancers, while the PSMB8 rs2071543 SNP was associated with increased risk of gastrointestinal and gynecological cancers, especially in Asian populations [17,28]; the meta-analysis did not report results related to bladder cancer. Besides its immune-related role in UBC, PSMB9 serves a clear role in intracellular protein degradation in neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being essential in cellular and immunological functions, the role of PSMB8 and PSMB9 has not been determined in all types of cancers, as highlighted in at least 78 publications [16], including 19 meta-analyses [17]. Few molecular genetics studies have focused on relationships between these i-proteasome genes and bladder cancer [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…For LMP7 rs2071543 , associated here with AD, it was reported that individuals with the TT genotype had a 3.5-fold higher ovarian cancer risk in Chinese people and 10-fold higher colon cancer risk in Germans than TG and GG genotypes [ 34 ]. The T allele was also found to be associated with cervical cancer similarly to LMP2 rs1351383*A [ 29 ], and, in a meta-analysis, also with other gynecological cancers as well as with gastrointestinal cancers [ 35 ]. In addition, the LMP7 rs2071543*TT genotype had a negative effect on the treatment of chronic hepatitis C virus-infected patients with pegylated interferon-α and ribavirin [ 36 ].…”
Section: Discussionmentioning
confidence: 99%